Tribal scenario in the context of economic liberalisation and globalisation - Singh, Bhupinder (2007)
The plight of STs after sixty years of planned development, entailing huge investments in terms of manpower, material and financial resources, could be attributed to various causes. Interior, forested and rough lerrain may have inhibited reach. Cultural barriers may have stood in the way of tribal acceptance of modern ideas and technology. But it looks that more than other factors, the official change and development agents have failed. STs have ever remained on the ring-side watching the development opera, not feeling allured enough to participate in it. The scenario impels a paradigm shift. The present moment, i.e., the commencement of the Eleventh Plan, is the opportune occasion to launch the shift. This paradigm shift in the Eleventh Plan period should offer the tribes people with unlimited opportunities to shape their future. Education should be the key sector and people-oriented purposeful action - a key element in the scenario. The approach will building enormous social capital. At the same time, it will make a vital contribution towards making the Indian society a knowledge society. - Reproduced.
Keywords: Globalization - India; Economic liberalization - India; Tribes - India; Tribes